Modeling of Heterogeneous Hydrodynamics Processes with Phase Transition (Моделювання, керування та інформаційні технології, 2019)
A new mathematical and numerical method of modeling for heterogeneous hydrodynamics processes with take of phase transitions like graphite-diamond will be presented. The method is based on an approximation of conservation laws for masses, momentums, and energies in integral and differential forms. The combination of Harlow's particle-in-cell method and Belotserkovskii's large particles method is used for computing by the modeling method simulation.